Ibn Sina’s Philosophy of Islamic Education: Concept, Purpose, and Character Formation in the Digital Age - Fathur Raman (Global Journal of Islamic Education, 2025)
In the era of digitalization, the concept and goal of Islamic education in developing student character has a significant impact on educational growth. In order for students to be prepared for the digital era with better integrity, competence, and good character, educators must be cautious in the learning techniques and curriculum that are taught to the students.  This is in line with the idea put forth by the scientist Ibn Sina that moral education should be emphasized together with attempts to prepare a person to live in society while engaging in the career or field of expertise of their choice based on their talents and ability. The goal of this research is to help students reach their full potential in terms of physical, intellectual, and character development. The descriptive qualitative method was applied in this study, and the data was gathered through a literature review. According to the findings of this study, teachers must adopt practical teaching techniques and curriculum, as well as divide learning grade levels based on student age and ability, and teachers must familiarize themselves with examples of excellent behaviour and character in the presence of students every day